Socio-demographic factors influences on guardians' perception of Developmental Coordination Disorder among Brazilian schoolchildren - Jorge Lopes Cavalcante Neto; Tatiana de Oliveira Sato; Eloisa Tudella (Universidade Estadual Paulista (UNESP), 2018)
Abstract AIM The objective of this study was to identify socio-demographic factors that are associated with the guardians' perception of developmental coordination disorder among schoolchildren from seven to ten years old. METHODS The parents/guardians of 361 children completed the Developmental Coordination Disorder Questionnaire (DCDQ) and a socio-demographic questionnaire in this cross-sectional study. The univariate relationship between the DCDQ and socio-demographic factors was tested by the chi-square test. The odds ratio (OR) with 95% confidence interval was calculated. Socio-demographic variables with p≤0.20 were included in the logistic regression analysis. RESULTS The child's age (B = 0.40; OR = 1.49; p <0.01) and the guardian undergoing treatment for illness (B = 0.97; OR = 2.65; p = 0.02) were retained in the final regression model. CONCLUSION Thus, increasing children's' age and guardians undergoing treatment for illness increased the guardians'perception of developmental coordination disorder.